Efeito da fotobiomodulação associada a fibra de carbono ativada no processo de reparo ósseo: modelo experimental - Dalmaso, Rachel Bharbara Maccheronio (2017)
Bone repair is a process that comprises aspects of skeletal development and growth, involving various extracellular components, cellular and growth factors. The intervention by external agents to accelerate bone repair becomes interesting for the possibility of rehabilitation and return of these patients to their normal activities. The importance of the use of non-medicated therapies, among them, photobiomodulation, represents a highly relevant factor for the health system. The objective of this work was to evaluate the effect of low intensity laser therapy associated or not with activated carbon fiber in the bone repair process. 64 male Wistar rats were distributed in 8 groups: Control (CTL), Untreated bone defect (NT), treated with 830nm, 1J, 100mW (L1J), treated with Laser 3J (L3J), and treated with Laser 6J (L6J), and treated with 10J Laser (L10J). After selecting the best paramete, 2 groups were evaluated: group with bone defect and use of activated carbon fiber (FA), and group with bone defect and use of activated fiber associated with 830nm, 6J, 100mW (AF + L) laser. Histological, morphological, biochemical and biomechanical modifications were evaluated. Results: L6J group presented a better histological aspect of bone repair, compared to the other irradiation parameters. The results showed an increase in the flexion strength in the L6J and AF + L groups compared to the NT group, an increase in the strain in the AF group compared to the NT group, a decrease in the alkaline phosphatase concentration in the L6J group compared to the group NT and histological analysis with the presence of an organized bone tissue in the L6J group with acceleration in the bone repair. This study shows the potential of the combination of photobiomodulation with activated carbon fiber as an effective tool in the repair of bone tissue.